Human factors handbook for process plant operations : improving process safety and system performance (John Wiley & Sons, Inc., 2022)
"The aim of this book is to help supervisors, managers and engineers incorporate Human Factors principles and practices in the design of processes and work tasks performed by plant maintenance and operations workers, enabling everyone to perform their work safely and effectively. The scope of this book covers all Human Factors subjects as applicable to the process industries, including using the framework of Crew Resource Management (CRM) which is used in the aviation industry. Although the primary focus is on Human Factors applications for plant operations and maintenance, it also covers the applications in the plant design phase, which must consider how lack of Human Factors considerations during the engineering design phase can adversely affect safety during operations and maintenance. Each Human Factors concept is introduced enlivened with anecdotes and case studies of real events from the process industries to illustrate key aspects of Human Factors."--